Establishment of a procedure to determine the content of 17 amino acids in soft-shell crab (Scylla sp.) - Lan, Nguyen Phuong; Trung, Do Thi Thanh; Vu, Van Thu; Thanh, Le Tat (Vietnam Journal of Biotechnology, 2020)
Mud crab Scylla sp. is a common sea crab species in Vietnam as well as in Asia Pacific. Today, mud crabs are raised on a large scale to be harvested at the soft molting stage because of the high economic value of the finished shell crabs. At present, the processing of soft shell crabs is limited to whole packaging and exporting. However, 30% of soft-shelled crabs in processing often lose their feet and claws, which reduce production costs. Therefore, it is necessary to study the technology of processing soft-shell crabs to improve the value of soft-shelled crab products. Recently, the application of enzymes in processing has brought many benefits such as being environmentally friendly and creating many bioactive substances. In this journal, we built the procedure to determine amino acid content in the processing of Scylla sp. to ensure the quality of products obtained after processing. This procedure based on HPLC using a fluorescence reader. The results showed that the amino acid content after hydrolysis process by enzyme technology reached 65.58% dry weight and contains many valuable amino acids such as lysine, leucine, valine, methionine, histidine.